Quality of Life in Heart Failure Patients: The Effect of Anxiety and Depression (Patient–Caregiver) and Caregivers’ Quality of Life - Athanasia Tsami; Ioannis Koutelekos; Georgia Gerogianni; Georgios Vasilopoulos; Niki Pavlatou; Antonia Kalogianni; Theodore Kapadochos; Angleliki Stamou; Maria Polikandrioti (Journal of Cardiovascular Development and Disease)
Patients with heart failure (HF) and their caregivers are a dyad inextricably linked that exert influence on patients’ quality of life (QoL). Purpose: The aim of this study was to explore factors affecting HF patients’ QoL. Factors were: (a) HF patients’ characteristics, (b) anxiety/depression of the dyad (patient–caregiver) and (c) caregivers’ QoL. Material and Methods: In this cross-sectional study, we enrolled 340 patients and 340 caregivers. Data collection was performed by the method of an interview using “The Hospital Anxiety and Depression Scale”, HADS) to assess anxiety and depression (patient–caregiver) as well as the “Minnesota Living with Heart Failure” and the “SF-36 Health Survey (SF-36)” to assess QoL (patient–caregiver, respectively). Results: From the 340 dyads who comprised the sample, 81.3% and 77.5% of patients experienced anxiety and depression, respectively, while 79.3% and 62.2% of caregivers experienced anxiety and depression, respectively. A statistically significant difference between patients and caregivers was only detected for depression (p = 0.001) and not for anxiety (p = 0.567). Patients with scores in HADS that indicate anxiety and depression had a worse QoL (total, physical, and mental). All subscales of the caregiver’s QoL were significantly associated with the patient’s QoL (p < 0.001) apart from the physical functioning scale. The correlation coefficients were all negative, indicating that a better caregiver’s QoL (higher SF36 scores) is associated with a better patient’s QoL (lower Minnesota scores). After controlling for the patient’s characteristics, the anxiety and depression of caregivers did not affect the patient’s QoL (confounding effect) whereas the patient’s anxiety/depression remained significant factors. Patients with anxiety and depression had 5.58 and 6.49 points, respectively, higher QoL score, meaning a worse QoL, compared to those with no anxiety/depression. Conclusions: Evaluating the impact of HF on patients’ QoL and anxiety/depression along with their caregivers permits acknowledgment of this dyadic relationship.